Analisis Film Suzanna: Malam Jumat Kliwon dalam Perspektif Kajian Sastra Feminisme - Francisco Harianto Simanjuntak (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the representation of women’s oppression in the film Suzanna: Malam Jumat Kliwon from the perspective of feminist literary criticism. The film is positioned as a literary text that represents power relations, gender inequality, and patriarchal domination within family and social structures. The research employs a descriptive qualitative approach using observation and note-taking techniques on scenes, dialogues, and narrative structures related to the position of the female character. The findings indicate that the character Suzanna experiences structural oppression due to the strong patriarchal system legitimized through economic pressure and family relations. Suzanna is positioned as an object of decision-making, deprived of voice and agency in determining her future, and forced to marry a much older man to settle her parents’ debts. This marriage reflects patriarchal practices that commodify women’s bodies and futures as instruments of social transactions. From the perspective of feminist literary criticism, the oppression experienced by Suzanna is not the result of individual weakness, but rather the consequence of unequal social structures that place women in subordinate positions. Thus, Suzanna: Malam Jumat Kliwon not only presents a horror narrative, but also serves as a medium of social criticism against gender injustice that continues to be reproduced in patriarchal society.